Ultrasound Imaging on Picture Archiving and Communication Systems: Are Radiologists Satisfied?. (1st August 2013) - Emerson, Donald S.; Cohen, Harris L.; Parks, Frank; Wan, Jim Y.; Graves, Houston
Abstract : Objectives: To evaluate whether picture archiving and communication systems (PACS) adequately satisfy radiologists' needs in ultrasound (US) imaging and which PACS functions may be inadequately implemented for handling US diagnosis. Methods: An electronic survey was sent to the membership of the Society of Radiologists in Ultrasound asking them to rate their PACS experience for different modalities, judge the quality of various PACS functions having an impact on US practice and diagnosis, indicate if they felt a need for US‐related PACS functions to be implemented or improved, and rate PACS‐related improvements for different components of their US practice. Results: Of the 161 respondents, 112 (70%) used a general radiology PACS. Of these respondents, only 53.2% gave a high rating to the US experience in PACS, significantly lower ( P < .0001) than for computed tomography (85.2%), magnetic resonance imaging (84.4%), and radiography (83.2%). The functionality of US‐specific display, image‐processing, and data management PACS processes were graded significantly lower than basic PACS display functions. Only 0.9% of respondents highly rated PACS handling of 3‐dimensional US volume data, whereas 92% highly rated the quality of the black‐and‐white US image display ( P < .0001). Most respondents would like most of these US‐specific functions implemented or improved, and most respondents stated that PACS has improved their US practice in different ways, although the contribution in more complex image analysis is lagging. Conclusions: Radiologists with a special interest in US believe that the PACS experience for US is lacking. This research helps identify those specific tasks that may further improve work efficiency and diagnostic confidence.